Roles, outcomes, and enablers within research partnerships: A rapid review of the literature on patient and public involvement and engagement in health research - Anne Wettergren Karlsson; Anne Kragh-Sørensen; Kirsten Børgesen; Karsten Erik Behrens; Torben Andersen; Maiken Langhoff Kidholm; Mette Juel Rothmann; Marjolijn Ketelaar; Astrid Janssens (Research Involvement and Engagement, 2023)
Abstract Background Recent studies mention a need to investigate partnership roles and dynamics within patient and public involvement and engagement (PPIE) in health research, and how impact and outcomes are achieved. Many labels exist to describe involvement processes, but it is unknown whether the label has implications on partnerships and outcomes. This rapid review investigates how roles between patients, relatives and researchers in a broad variety of PPIE activities in health research are described in peer reviewed papers and explores what enables these partnerships. Methods Rapid review of articles published between 2012 and February 2022 describing, evaluating, or reflecting on experiences of PPIE in health research. All research disciplines and research areas were eligible. Four databases (Medline, Embase, PsychInfo and CINAHL) were searched between November 2021 and February 2022. We followed PRISMA guidelines and extracted descriptive factors: year, origin, research area and discipline, study focus, framework used and co-authorship. On a selection of articles, we performed a narrative analysis of partnership roles using Smits et al.’s. Involvement Matrix. Lastly, we performed a meta synthesis of reported enablers and outcomes of the partnerships. Patients and Relatives (PRs) have been involved in the whole rapid review process and are co-authors of this article. Results Seventy articles from various research disciplines and areas were included. Forty articles were selected for a narrative analysis of the role description of PRs and researchers, and a meta synthesis of enablers and outcomes. Most articles described researchers as decision-makers throughout the research cycle. PRs most often were partners when they were included as co-authors; they were mostly partners in the design, analysis, write-up, and dissemination stages. Enablers of partnerships included: PR training, personality of PRs and communication skills, trust, remuneration and time. Conclusions Researchers’ decision-making roles gives them control of where and when to include PRs in their projects. Co-authorship is a way of acknowledging patients’ contributions which may lead to legitimation of their knowledge and the partnership. Authors describe common enablers, which can help future partnership formation.